Does Pulsed Magnetic Field Therapy Influence Nerve Regeneration in the Median Nerve Model of the Rat?. (21st July 2014) - Beck-Broichsitter, Benedicta E.; Lamia, Androniki; Geuna, Stefano; Fregnan, Federica; Smeets, Ralf; Becker, Stephan T.; Sinis, Nektarios
Abstract : The aim of this study was to evaluate the impact of pulsed magnetic field therapy on peripheral nerve regeneration after median nerve injury and primary coaptation in the rat. Both median nerves were surgically exposed and denervated in 24 female Wistar rats. A microsurgical coaptation was performed on the right side, whereas on the left side a spontaneous healing was prevented. The study group underwent a daily pulsed magnetic field therapy; the other group served as a control group. The grasping force was recorded 2 weeks after the surgical intervention for a period of 12 weeks. The right median nerve was excised and histologically examined. The histomorphometric data and the functional assessments were analyzed by t -test statistics and one-way ANOVA. One-way ANOVA indicated a statistically significant influence of group affiliation and grasping force ( P = 0.0078 ) . Grasping strength was higher on a significant level in the experimental group compared to the control group permanently from the 9th week to the end of the study. T -test statistics revealed a significantly higher weight of the flexor digitorum sublimis muscle ( P = 0.0385 ) in the experimental group. The histological evaluation did not reveal any statistically significant differences concerning the histomorphometric parameters. Our results suggest that the pulsed magnetic field therapy has a positive influence on the functional aspects of neural regeneration. More studies are needed to precisely evaluate and optimize the intensity and duration of the application.